Hydrogen adsorption on graphene-based materials - Holec, David (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2022)
In the light of present energy crisis, questions related to alternative resources are becoming more important than ever before. Hydrogen-based technology is an appealing option. However, a wider spread of this technology will not be possible without appropriate storage capacities. In the present work we employ atomistic calculations to reveal adsorption mechanisms of H in graphene-based materials. Namely, we employ density functional theory to study impact of metallic catalysts on the adsorption energies of H on graphene. Additionally, interplay between H adsorption and structural defects in graphene (vacancies, Stone-Wales defects, etc.) will be discussed. Lastly, we will present results of grand canonical Monte Carlo simulations comparing adsorption capabilities of pristine graphene and a recently theoretically proposed graphene-polymorph, so-called Penta-Octa-Penta (POP) graphene.